The Influence of Innovative Characteristics, Work Readiness, and Vocational Self-Concept on Employability of Vocational College Students - Ahmid, Suhailah Sahul; Tiew, Chia Chun; Abdullah, Melissa Ng Lee Yen (International Journal for Research in Vocational Education and Training, 2023)
Purpose: Vocational education and training is important to produce skilled and innovative labor to drive the country's development in the 4th industrial revolution (IR 4.0). The employability of vocational college students is crucial to meet the country's demand for 21st-century workers. This study aims to identify the influences of innovative characteristics, work readiness, and vocational self-concept on the employability of vocational college students. The study also examined the moderating role of gender. Methods: A quantitative correlational design was carried out to achieve the objectives of the study. The samples consisted of 395 vocational college students from five vocational colleges located in the states of Kedah and Penang, Malaysia. Data were collected through online questionnaire survey, which is made up of four instruments: Youth Innovation Skills Measurement Tool, the Work Readiness Scale, the Vocational Rational Scale and the Perceived Future Employability Scale. The validity and reliability of these instruments were well established. Descriptive and structural equation modelling (SEM) analyses were carried out. Findings: Innovative characteristics (β = 0.252, t = 5.041, p < 0.001), vocational self-concept (β = 0.386, t = 7.131, p < 0.001) and work readiness (β = 0.219, t = 3.787, p < 0.001) had significant effects on employability of vocational college students. The model explained 53% of the variance in employability. Gender, however, did not moderate any of the three direct significant relationships. Conclusion: This study found that innovative characteristics, work readiness, and vocational self-concept are factors that should be taken into consideration when developing education and career programs, interventions, and support services for vocational students. The graduate employment issues faced by vocational college students can be overcome if factors identified in this study can be enhanced. Similar approaches can be applied for both male and female students since gender is not a significant moderator. Overall, this study sheds light on the employability of vocational graduates and contributes towards improving career guidance and counseling practices for vocational students.